Genetic diversity and relationships of hair sheep breeds of the Americas: First results - Muigai, Anne W.T.; Hirbo, J.; Sharkey, S.; Rege, J.E.O.; Blackburn, H.; Hanotte, Olivier H. (Institut National de la Recherche Agronomique, 2002)
The origin of the American hair sheep is diverse with likely early introductions from the Canary Islands, followed by introductions from the African and European continents. Using 14 microsatellite loci, we studied 3 American hair sheep (St. Croix, Barbados Blackbelly, and Gulf Coast Native), 6 European wool sheep, 6 African hair sheep, and 2 Asian wool sheep populations. The genetic diversity for all populations was high (with the exception of the Barbados Blackbelly where n=10). Phylogenetic and principal component analyses as well as genetic distance values indicated that the American hair sheep were more closely related to the European Merino sheep than to the West African hair sheep. Today, the main genetic influence in the 3 American populations studied is therefore of European origin.